THE ROLE OF THE INNOVATIVE EDUCATION CLUSTER IN THE PROCESS OF FORMING THE PROFESSIONAL COMPETENCES OF DEFECTOLOGISTS (Web of Teachers: Inderscience Research, 2024)
This article describes the ways to develop the professional competencies of future speech pathologists, the innovative cluster of pedagogical education, all types of education in the system of continuing education, research institutes and centers, practice bases, the integrity of scientific and scientific-methodological structures. It is said that it will allow to raise the system to a qualitatively new level.